On Construction of Mean Graphs (Journal of Scientific Research, 2013)
A graph with p vertices and q edges is called a mean graph if there is an injective function f  that maps V(G) to  such that for each edge uv, is labeled with     if    is even and  if  is odd. Then the resulting edge labels are distinct. In this paper, we prove some general theorems on mean graphs and show that the graphs , Jewel graph , Jelly fish graph and  are mean graphs.Keywords:  Mean labeling; Mean graph.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.11545             J. Sci. Res. 5 (2), 265-273 (2013)